Stabilizing Organic–Inorganic Lead Halide Perovskite Solar Cells With Efficiency Beyond 20% - Lin, Ching (Frontiers in Chemistry, 2020)
The power conversion efficiency (PCE) of organic-inorganic lead halide perovskite solar cells (PSCs) has exceeded 25%, approaching the best record of their silicon counterpart. However, lifetime issues still stand between PSCs and the goal of mass commercialization. For instance, most photoactive perovskites are hydrophilic, and moisture can quickly turn some of their constituents to compounds yielding trap states. Some perovskites are not thermally stable in the temperature window of solar cell operation and will transform into photo-inactive non-perovskites. If a perovskite is of an inadequate quality, e.g., vacancies, surface area, or grain boundaries per unit volume is high, there exist more defect sites, acting as migration pathways for perovskite ions under photo-bias, and the migration changes the perovskite’s composition. An unstable perovskite/charge transport material (CTM) interface allows cross-contamination between molecules from both sides of the interface. Even without external stress, perovskite ions in an operating PSC undergo redox processes, which create defect states or initiate chemical chain reactions to accelerate PSCs degradation. This mini-review discussed recent progress in solving issues, including the above, to stabilize PSCs with competitive PCE beyond 20%. The remarkable longevity of 15 PSCs under accelerated aging tests was probed in depth from three viewpoints: (1) perovskite compositions and dopants, (2) perovskite additives, and (3) CTMs. This mini-review, within which crucial perovskite-stabilizing methods were systematically analyzed, can be used as a quick-start guide when dealing with PSCs’ stability in the future.